IncHI2 Plasmids Are Predominant in Antibiotic-Resistant Salmonella Isolates - Chen, Wenyao; Fang, Tingzi; Zhou, Xiujuan; Zhang, Daofeng; Shi, Xianming; Shi, Chunlei (Frontiers in Microbiology, 2016)
The wide usage of antibiotics contributes to the increase in the prevalence of antibiotic-resistant Salmonella. Plasmids play a critical role in horizontal transfer of antibiotic resistance markers in Salmonella. This study aimed to screen and characterize plasmid profiles responsible for antibiotic resistance in Salmonella and ultimately to clarify the molecular mechanism of transferable plasmid-mediated antibiotic resistance. A total of 226 Salmonella isolates were examined for antimicrobial susceptibility by a disk diffusion method. Thirty-two isolates (14.2%) were resistant to at least one antibiotic. The presence of plasmid-mediated quinolone resistance (PMQR) genes and β-lactamase genes were established by PCR amplification. PCR-based replicon typing (PBRT) revealed that these 32 isolates represented seven plasmid incompatibility groups (IncP, HI2, A/C, FIIs, FIA, FIB, and I1), and the IncHI2 (59.4%) was predominant. Antibiotic resistance markers located on plasmids were identified through plasmid curing. Fifteen phenotypic variants were obtained with the curing efficiency of 46.9% (15/32). The cured plasmids mainly belong to the HI2 incompatibility group. The elimination of IncHI2 plasmids correlated with the loss of β-lactamase genes (blaOXA-1 and blaTEM-1) and PMQR genes (qnrA and aac(6’)-Ib-cr). Both IncHI2 and IncI1 plasmids in a S. enterica serovar Indiana isolate SJTUF 10584 were lost by curing. The blaCMY-2-carrying plasmid pS10584 from SJTUF 10584 was fully sequenced. Sequence analysis revealed that it possessed a plasmid scaffold typical for IncI1 plasmids with the unique genetic arrangement of IS1294-△ISEcp1-blaCMY-2-blc-sugE-△ecnR inserted into the colicin gene cia. These data suggested that IncHI2 was the major plasmid lineage contributing to the dissemination of antibiotic resistance in Salmonella and the activity of multiple mobile genetic elements may contribute to antibiotic resistance evolution and dissemination between different plasmid replicons.